First description of the karyotype and localization of major and minor ribosomal genes in Rhoadsia altipinna Fowler, 1911 (Characiformes, Characidae) from Ecuador - Sanchez-Romero, Omar; Abad, Cesar Quezada; Cordero, Patricio Quizhpe; Sene, Viviani Franca de [UNESP]; Nirchio, Mauro; Oliveira, Claudio [UNESP] (Pensoft Publ, 2015)
Karyotypic features of Rhoadsia altipinna Fowler, 1911 from Ecuador were investigated by examining metaphase chromosomes through Giemsa staining, C-banding, Ag-NOR, and two-color-fluorescence in situ hybridization (FISH) for mapping of 18S and 5S ribosomal genes. The species exhibit a karyotype with 2n = 50, composed of 10 metacentric, 26 submetacentric and 14 subtelocentric elements, with a fundamental number FN=86 and is characterized by the presence of a larger metacentric pair (number 1), which is about 2/3 longer than the average length of the rest of the metacentric series. Sex chromosomes were not observed. Heterochromatin is identifiable on 44 chromosomes, distributed in paracentromeric position near the centromere. The first metacentric pair presents two well-defined heterochromatic blocks in paracentromeric position, near the centromere. Impregnation with silver nitrate showed a single pair of Ag-positive NORs localized at terminal regions of the short arms of the subtelocentric chromosome pair number 12. FISH assay confirmed these localization of NORs and revealed that minor rDNA clusters occur interstitially on the larger metacentric pair number 1. Comparison of results here reported with those available on other Characidae permit to hypothesize that the presence of a very large metacentric pair might represent a unique and derived condition that characterize one of four major lineages molecularly identified in this family.
Keywords: 18S and 5S ribosomal genes; C-bands; fishes; Karyotype; NORs